Empowerment of Tourism Awareness Groups in the Panbo Beach Area in an Effort to Improve Website-based Tourism Management - Helly Aroza Siregar; Suroyo Suroyo; M Hasmil Adiya; M Noval Dwi Pratama; Nadira Nurul Atika (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
To organize tourism in an effort to increase national income, expand and equalize business opportunities and employment opportunities, which encourage regional development. The purpose of this study is to increase national income, expand and equalize business opportunities and employment, which encourages regional development, introduces and utilizes tourist attractions and destinations in Kampar Regency. The location is in the Panbo area, Batu Bersurat village. This research is a research and development with the implementation of a website-based information system with the subject of a tourism-aware group on Panbo Beach. Data collection tools in the form of field observations and pre-interviews to find problems in the field. The technology proposed to assist partners in solving partner priority problems, namely marketing problems, by introducing and marketing Panbo Beach through website-based marketing to make it easier for tourists to get to know Panbo Beach and make it easier for management to manage. The results of a website-based information system with the aim of making it easier for tourism-aware people to manage Panbo Beach tourist destinations with the current system, in addition, management of destination areas and promotion of tourism media are also part of the ease of use of web-based information systems.